2004
DOI: 10.1515/jpm.2004.132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between HELLP syndrome, chronic hypertension, and superimposed preeclampsia on chronic hypertension without HELLP syndrome

Abstract: Perinatal outcome is primarily influenced by gestational age at delivery and birthweight independent of the severity of the hypertensive status of pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
3
16
0
5
Order By: Relevance
“…Some studies have shown that perinatal morbidity was higher in patients with HELLP syndrome than in those with hypertension alone (15,16). However, there are further studies showing that gestational age was more effective than maternal disease for perinatal outcomes (7,(17)(18)(19). In two studies, neonatal death rates were not different between HELLP syndrome and severe preeclampsia at the same stage of gestation (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that perinatal morbidity was higher in patients with HELLP syndrome than in those with hypertension alone (15,16). However, there are further studies showing that gestational age was more effective than maternal disease for perinatal outcomes (7,(17)(18)(19). In two studies, neonatal death rates were not different between HELLP syndrome and severe preeclampsia at the same stage of gestation (7,20).…”
Section: Discussionmentioning
confidence: 99%
“…As Tabelas 1 e 2 apresentam estudos realizados com mulheres que desenvolveram pré-eclâmpsia sobreposta à hipertensão crônica. Tiveram agravos no resultado materno e perinatal 20% a 78%, incluindo restrição do crescimento fetal (8,5% a 30,7%), prematuridade (32,4% a 86,4%), parto cesarea (69,2%), descolamento prematuro da placenta (3,75% a 8,4%), óbito fetal (9,5% a 27,2%) e complicações cardíacas, vasculares, renais e pulmonares maternas (5)(6)(7)(8)10,16,(22)(23)26,28) . Em alguns trabalhos o número de hipertensas foi pequeno, sugestivo a critério diagnóstico de hipertensão crônica tabela 1 -Número de mulheres estudadas durante os anos de 1990 a 1999 e a ocorrência de complicações.…”
Section: Resultsunclassified
“…Este tipo de hipertensão pode ser primá-ria ou essencial, esta representada por 90% dos casos e secundária, incluindo desordens renovasculares, coarctação da aorta, distúrbios endócrinos e doenças vasculares do colágeno (3,(7)(8) .…”
Section: Introductionunclassified
“…If the maternal conditions alter, caesarean section is inevitable (1,31,32,33). Some authors warn against conservative management and contraindicate it (34).…”
Section: Management Of Hellpmentioning
confidence: 99%